THE MULTIPLICITY OF ETHNIC IDENTITIES: INDONESIANS IN MELBOURNE - Deddy Mulyana (Universitas Padjadjaran, 2002)
This research aims to demonstrate how the Indonesian migrants in Melbourne construct their Indonesian identity based on the theoretical perspective of George Herbert Mead, Erving Goffman, and Fredrik Barth. To collect the data the researcher used the qualitative research method composed of participant observation and in-depth interviews. The quota sampling and the snowball sampling were carried out to select the key informants, that is, the Indonesian migrants who come from various socio-cultural backgrounds, most of them being Malay Indonesians who have lived in Australia for a long time. The results of the research indicate that the Indonesian identity in Melbourne is composed of several categories, each of which having its respective boundary. Thus, ethnic identity is dynamic and fluid to fit a particular situation. Some of the subjects performed impression management and passing in their interaction with others. Key words : Ethnic boundary, ethnic category, impression management, passing